Improving fertility, seed composition, and yield in soybean through strategic Diethyl aminoethyl hexanoate (DTA-6) application - Huda Hussein Neamh Almossawi; Ali Nadhim Farhood; Omar Mahmoud Dhannoon (Journal of Kerbala for Agricultural Sciences, 2025)
This study investigated the effect of the growth regulator DTA-6, applied at varying concentrations (30, 60, and 90 mg L⁻¹) during two critical growth stages—branching (GS-22) and flowering (GS-51)—on the productivity and quality attributes of two locally adapted soybean cultivars (Shaima and Abaa). Results revealed that DTA-6 positively influenced several agronomic traits, including fertility percentage, seed yield, and various seed quality parameters such as oil content and fatty-acid composition. Notably, the highest DTA-6 concentration (90 mg L⁻¹), when applied at the flowering stage, yielded the most significant improvements in fertility percentage, seed yield, and certain fatty-acid profiles, albeit accompanied by a reduction in protein content. Genetic differences between the two cultivars—Shaima and Abaa—clearly influenced their responses to DTA-6. Shaima excelled in seed yield and exhibited lower seed wrinkling along with higher oil and oleic acid content, suggesting an enhanced genetic capacity for efficient resource allocation and lipid biosynthesis. In contrast, Abaa showed superior fertility percentage and higher protein content, likely due to genetic traits favoring reproductive development and nitrogen assimilation. These findings underscore the importance of selecting suitable cultivars and optimizing the timing of DTA-6 application to maximize agronomic and quality-related benefits. A significant interaction between cultivar, application timing, and DTA-6 concentration was observed, highlighting that the response varied according to the genetic background and treatment combination. Consequently, the strategic integration of DTA-6 into soybean crop management could enhance yield and seed quality, paving the way for more efficient and profitable production in environments like those studied.